Effect of Whey Protein Concentrate and Little Millet Flour on the Sensory Attributes of Low-Fat Greek Yoghurt Spread - Sweety,; , Asif Ali T S; , Aiswarya Velekat Santhosh; Harinivenugopal, (Archives of Current Research International, 2025)
Aims: To develop and evaluate a low-fat functional Greek yoghurt spread by incorporating whey protein concentrate (WPC) and little millet flour, assessing their impact on sensory and overall acceptability characteristics. Study Design: A completely randomized design (CRD) was employed to evaluate the effect of different concentrations of WPC (1%, 2%, 3%) and little millet flour (1%, 2%, 3%) on the sensory attributes of Greek yoghurt spread. Place and Duration of Study: The study was carried out at the Department of Dairy Technology, Dairy Science College, Hebbal, Bengaluru, Karnataka, India, during the period from January 2024 to October 2024. Methodology: Fresh cow milk (4.0% fat) was standardized and pasteurized to 90ºC before incorporating varying concentrations of WPC (@1, 2, and 3%). Greek yoghurt was prepared by fermentation using commercial starter cultures (Streptococcus thermophilus and Lactobacillus delbrueckii subsp. bulgaricus). The fermented yoghurt was drained to achieve a concentrated Greek yoghurt, which was emulsified with 45% butter and little millet (@1, 2, and 3%). Sensory evaluations were performed using a 9-point hedonic scale by trained panelists. Statistical analysis of data, including ANOVA and critical difference (CD), was carried out using R software (version 4.1.2). Results: Effect of WPC: Greek yoghurt with 2% WPC demonstrated superior sensory attributes, including flavor (8.66), color and appearance (8.45), texture (8.41), spreadability (8.62), and overall acceptability (8.41). Higher WPC concentrations resulted in a bitter taste and yellowish hue. Effect of Little Millet: Greek yoghurt spread with 2% little millet achieved the highest sensory scores for flavor (8.71), color and appearance (8.54), texture (8.60), spreadability (8.53), and overall acceptability (8.51). Higher concentrations of millet resulted in a thicker texture, reducing spreadability and overall scores. Conclusion: The addition of WPC and little millet flour significantly improved the sensory qualities and overall appeal of the low-fat functional Greek yogurt spread. This innovative formulation presents a healthier and more functional option compared to traditional spreads, aligning with the growing consumer preference for nutritious alternatives. Enriching the spread with WPC and little millet flour boosts its protein content and delivers numerous health advantages. WPC contributes to muscle recovery, supports immune health, and promotes tissue repair, while little millet flour, packed with dietary fiber and antioxidants, aids in digestion, helps regulate blood sugar levels, and reduces the risk of chronic illnesses. This formulation is a wholesome, heart-friendly, and weight-conscious choice for health-conscious consumers.